(untitled) (Journal of Computational Mathematics, 2001)
Based on the generalized Dikin-type direction proposed by Jansen et al in 1997, we give out in this paper a generalized Dinkin-type affine scaling algorithm for solving the P_*(k)-matrix linear complementarity problem (LCP). By using high-order correctors technique and rank-one updating, the iteration complexity and the total computational turn out asymptotically O((κ+1)nL) and O((κ+1)n^3L) respectively.